4. KEKERASAN DALAM PILKADA DI ACEH PASCA MOU - HP, Shary Charlotte (FORUM, 2014)
This article is aimed to explain the causes of violence in post MoU's Aceh elections. Eventhough the separatist violence in Aceh was ended in 2005, but violent conflict in Aceh continues to increase and is often concentrated in the pre MoU conflict area. In post-conflict situations, the intensity of the conflict is much reduced; the conflict also becomes less latent, but rarely stops at all. If war has changed the habits and behavior of the people of Aceh to the dominance of violence, the peace treaty seeks to change the behavior, attitudes and contradictions of actors involved by using Disarmament, Demobilization and Reintegration programs. Issues and problems began to emerge in this long term process of reintegration programs. Reintegration program was initially planned to merge the former combatants and the civil societies, but in its progress, this program created a huge gap between them.. and thus encouraging a conflict-prone condition, especially during the eleetion.